Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan (Musrenbang) di Nagari Kamang Kabupaten Sijunjung - Rinita Rinita; Yuliarti Yuliarti (Al-DYAS, 2026)
Community participation is a key element in participatory development planning at the nagari (village) level, and the Musyawarah Perencanaan Pembangunan (Musrenbang) serves as a strategic forum for channeling citizens’ aspirations in the formulation of development programs. However, attendance and engagement levels among community members in the Musrenbang of Kamang Nagari, Sijunjung Regency, have shown a declining trend. This study aims to describe the level of community participation in the implementation of Musrenbang and to analyze the factors that influence such participation. This research employed a qualitative method with a descriptive approach, with data collected through interviews, observations, and document studies involving key informants consisting of the wali nagari, nagari officials, community leaders, and community members who participated and did not participate in Musrenbang. The findings indicate that community participation in the Musrenbang of Kamang Nagari remains relatively low at all stages, including attendance, expression of aspirations, and involvement in decision-making. This low participation is influenced by several key factors, namely limited nagari budgets, the dominance of government actors in the Musrenbang forum, low public trust in the follow-up of Musrenbang outcomes, and limited community understanding of the importance of participatory development planning. The study underscores the need to enhance budget transparency, strengthen community roles and capacities, and optimize the socialization of Musrenbang as practical implications for improving the quality of community participation in development planning at the nagari level.